A family of microscale 2 × 2 × 2 Pocket Cubes. Issue 36 (29th August 2017) - Aldossary, Minahi S.; Zhu, Jian; Porob, Rakesh R.; Deng, Da
Abstract : A family of Pocket Cubes with different chemical compositions but with the same overall mesoscale microstructures was prepared for potential applications in energy storage and water treatment. Abstract : Hierarchical microscale materials have received much attention recently. They can find many important applications, including wastewater treatment and energy storage. However, it is still a challenging task to facilely synthesize microscale structures with good size distribution, unique structures and, particularly, tunable composition. Herein, we have prepared a family of 2 × 2 × 2 Pocket Cube-like hierarchical microparticles, with different chemical compositions, including bimetal hydroxide (ZnSn(OH)6 ), mixed bimetal oxide and metal oxide (Zn2 SnO4 &SnO2 ), carbon coated bimetal oxide and metal (Zn2 SnO4 &Sn@C), all with the same overall mesoscale microstructures. This family of microscale Pocket Cubes, with different chemical compositions and their associated different physiochemical properties, may offer a set of functional materials for many applications. In order to demonstrate their potential applications, we have preliminarily studied their performances in rechargeable batteries and water remediation. Interestingly, these selected Pocket Cubes are electrochemically active toward the reversible storage of both sodium and lithium with comparable performances to those nanoparticles reported, although their sizes are remarkably large on the microscale. We found that the shapes of the microparticles can influence their photocatalytic performances. Our preliminary results suggest that this family of microscale Pocket Cubes, with further optimization and improvement, can find many promising applications, including wastewater treatment and energy storage.